Analisis Pesan Dakwah dalam Pembacaan Hizib Nahdlatul Wathan di Lingkungan Menang, Kelurahan Gerung Selatan, Lombok Barat - Dewi, Ayu Septiana (FONDATIA, 2025)
Da'wah is a noble activity aimed at promoting virtue and preventing vice to achieve happiness in both this world and the hereafter, as commanded in QS Ali Imran verse 104. In this context, the use of relevant da'wah media becomes essential, including through local religious traditions. This study aims to analyze the da'wah messages conveyed through the recitation of Hizib Nahdlatul Wathan (NW) in Lingkungan Menang, Gerung Selatan Subdistrict, Gerung District, West Lombok. This tradition is conducted in rotation from house to house as a form of cultural da'wah intended to strengthen faith and social solidarity. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The results show that the recitation of Hizib NW conveys da'wah messages encompassing three main aspects: aqidah (faith), syariah (Islamic law), and akhlak (moral behavior). In addition to conveying Islamic values, this activity contributes to strengthening social relationships, increasing spiritual awareness, preserving religious and local cultural traditions, and reducing the potential for social conflict within the community. These findings affirm that da'wah through the recitation of Hizib NW is not merely verbal but also practical, thereby simultaneously reinforcing the social and spiritual dimensions of community life.